2020
DOI: 10.36656/jpkm.v3i1.430
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Dukungan Keluarga Terha Hubungan Dukungan Keluarga Terhadap Perilaku Remaja Puteri Tentang Perubahan Fisik Pada Masa Pubertas Di SMP Negeri 1 Deli Tua Tahun 2020

Abstract: Teenagers, who are studying at Junior High Schools, are in their puberty. In general, teenagers undergo various problems and difficulties in adjusting themselves to their environment in their puberty. The objective of the research was to find out the correlation between family support and female teenagers behavior in their physical change in their puberty at SMP Negeri 1 Deli Tua tahun 2020. The research used an analytic method with cross sectional design. It was conducted in September 2014 to February 2015. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…This gender and age distribution aligns with previous studies that indicated a higher prevalence of gaming addiction among teenage males compared to females. 19,20 The analysis of playing duration revealed that most participants were regular gamers, spending between 2 and 7 hours per day playing Mobile Legends. This finding is consistent with previous studies indicating that regular gamers represent a significant portion of e-sports enthusiasts.…”
Section: Discussionmentioning
confidence: 99%
“…This gender and age distribution aligns with previous studies that indicated a higher prevalence of gaming addiction among teenage males compared to females. 19,20 The analysis of playing duration revealed that most participants were regular gamers, spending between 2 and 7 hours per day playing Mobile Legends. This finding is consistent with previous studies indicating that regular gamers represent a significant portion of e-sports enthusiasts.…”
Section: Discussionmentioning
confidence: 99%
“…Terlalu lama bermain game online dia mengatakan sering mengantuk, lelah dan kurang konsetrasi saat melakukan aktivitas di siang hari. Dia juga mengatakan dampak buruk yang disebabkan oleh kebiasaan bermain game online adalah terganggunya prestasi belajar yang sering mengabaikan tugas-tugas sekolah dan sering membolos saat jam sekolah karena mengantuk (Gurusinga, 2020).…”
Section: Hasil Dan Pembahasan Kecanduan Game Online Pada Remajaunclassified
“…Sepenting kebutuhan makan, beraktivitas, bernapas, seksual, dan kebutuhan lainnya. (Gurusinga, 2020) Berdasarkan tabel diatas menunjukan bahwa dari 56 orang responden tidak kecanduan game online dengan kualitas tidur baik sebanyak 2 orang (100,0%), responden tidak kecanduan game online dengan kualitas buruk sebnyak 0 orang (0,0%), responden kecanduan game online dengan kualitas tidur baik sebanyak 4 orang (50,0%), responden kecanduan game online dengan kualitas tidur buruk sebnyak 4 orang (50,0%), responden sangat kecanduan game online dengan kualitas tidur baik sebnyak 0 orang (0,0%), responden sangat kecanduan game online dengan kualitas tidur buruk sebanyak 46 orang (100,0%). Berdasarkan hasil uji stastistik Chi Squere dan pada derajat kepercayaan 95% dilakukan untuk mengetahui hubungan kecanduan game online dengan kualitas tidur remaja di SMAN 1 Cimaragas kelas XII diperoleh nilai P Value 0,00 (P ≤ 0,005).…”
Section: Introductionunclassified